IKAN YANG BERUAYA DI DAERAH MANGROVE PANTAI TASIK RIA - Otinus Lokbere; Farnis B Boneka; Chatrien A Sinyal; Billy Th Wagey; Medy Ompi; Rose OSE Mantiri (JURNAL PESISIR DAN LAUT TROPIS, 2019)
This study is intended to find out the fish that are cultured into the mangrove area of Tasik Ria beach, Mokupa, Minahasa Regency. Fish is obtained through gill jarring at high tide. The fish that were identified were Archamia fucata, Lutjanus fulvus, Lutjanus eherenbergii, Lethrinus ornatus, Scolopsis lineate, Sargocentron diadema, Epinephelus merra and Scorpaenopsis oxycephala. The fish are generally carnivorous, and are nocturnal.Key words: Tasik Ria Beach, the fishes, carnivorous, mangroves